The Impact of Academic Potential Test (APT) on GPA Score in Bachelor Dental Program in Trisakti University - Rahmi Amtha; Tri Erri Astoeti; Tri Putriany Agustin; Yohana Yusra; Wiwiek Poedjiastoeti; Indrayadi Gunardi (Indonesian Dental Association, 2019)
Introduction: Academic potential test (APT) is the terminology used for requirement in student recruitment process at Faculty of Dentistry, Trisakti University. According to literature, APT score is believed to predict the academic achievement in graduate school. Objectives: This study assessed the impact of APT score on GPA score at Bachelor Dental Program year 2015-2018. Methods: Cross sectional descriptive analysis were done on 486 students, divided into 4 groups based on credit semester (CS); group A 144 CS, B 100 CS, C 60 CS, and D 20 CS. Result: mean APT score were 598 + 95.46 and GPA score were 2.63 + 0.72. Linear regression test showed significant correlation between APT and GPA scores (p=0.007; r2=1.5%). It shows that APT contributed as only a little aspect for the success of students in their study. In dentistry, there are other factors that may influence GPA score beside APT such as intellectual quality, talent, behavior, psychomotor and capability in social, science and communication. Conclusion: Academic potential test could be used to predict the GPA score in Bachelor Dental Program.